A STUDY TO ASSESS THE EFFECTIVENESS OF BATES THERAPY ON VISUAL ACUITY AMONG OLD AGE PEOPLE RESIDING IN SELECTED OLD AGE HOME AT ERODE DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Aim: The main objectives of this study were to determine the effectiveness of Bates therapy on visual acuity, and to find out the association between pre-test and post-test scores on visual acuity among old age people. Methods: A quasi-experimental design was carried out on 60 old age people with visual problems residing in Assisi Karuna Nilaya, Buthikottai, Erode Dt. with 30 participants in the experimental group and 30 participants in the control groupby using a purposive sampling technique. Visual acuity assessment scale (Snellen chart) was used to assess the visual problems among old age people in pre and post-test. The experimental group received Bates therapy as an intervention. It is a series of 5 steps which includes stretching, blinking, swinging, sunning, and palming or cupping given for 15 minutes daily once and control group received no treatment, and a post-test was done after 15 days using a visual acuity scale.Results:          In the analysis of association between the post test score and their selected demographic variables among old age people with visual acuity. Chi square value of age in years was 0.119, gender was 0.039, educational status was 4.767, marital status was 1.862, diet is 0.027, watering of eye was 5.029, visual disturbance 1.833 and using spectacles are1.663. Conclusion: The result of the study showed that there was a higher incidence of visual acuity among the old age people aged above 60 years. The present study was intended to assess the effectiveness of Bates therapy on visual acuity among old age people residing in selected old age home at Erode District. The report of this study found that Bates therapy was inexpensive and more effective in improving visual acuity.